PENGARUH LEVERAGE, MANAJEMEN LABA, CAPITAL INTENSITY DAN KOMPENSASI RUGI FISKAL TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Manufaktur Sektoral Aneka Industri Yang Terdaftar di BEI tahun 2013-2016) - Septhea Dwi Pratiwi; Enni Savitri; Supriono Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study is aims to analyze and provide empirical evidence of the (1) influence of leverage of of tax aggressiveness, (2) influence of earnings management of tax aggressiveness, (3) influence of capital intensity of tax aggressiveness and (4) influence of tax loss compensation of tax aggressiveness. The population is used to various industry sectoral manufacturing companies on the Indonesian stock exchanges for the period 2013-2016. The sample method is purposive sampling with result of selection of 43 data. Data analysis is used by multiple linear regression. The results of this study proves Leverage has an effect on tax aggressiveness. Earnings Management has an effect on tax aggressiveness. Capital intensity has no effect on tax aggressiveness. Tax loss compensation has no effect on tax aggressiveness.Keywords : Leverage, Earnings Management, Capital Intensity, Tax Loss Compensation, and Tax Aggressiveness.